1998
DOI: 10.1017/s1742758400007797
|View full text |Cite
|
Sign up to set email alerts
|

Pesticidal potential of tropical plants—II. Acaricidal activity of crude extracts of several Jamaican plants

Abstract: Topical application of crude ethanol extracts (CEs) of the leaves of 43 of 51 Jamaican plants produced varying degrees of multiple acaricidal effects on engorged Boophilus microplus Canst., including mortality (M), inhibition of oviposition (IO) and inhibition of embryogenesis (IE). Acaricidal indices (AI) ranged from 50 to 100 for the CEs of 29 plants, 38 to 47 for 9 plants and from 0 to < 25 for 13 plants. The most active CEs, in decreasing order of activity (AI values in parentheses) were those of: Simaroub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
(28 reference statements)
1
7
0
Order By: Relevance
“…Efforts to promote hands-on use of antitick plants at community level have clearly increased as signaled by a worldwide documentation of the plants (Tables 2 and 3) and many more studies being conducted on field surveys and trials [58, 109, 122, 129, 149] and laboratory tests [73, 96, 215220]. The ongoing workshops, community-based training seminars, and novel projects on antitick plants at the Intermediate Technology Development Group-Eastern Africa (ITDG-EA), an international nongovernmental organization [129], are other promising proliferation signals in this area.…”
Section: Potential and Future Prospects For The Use Of Antitick Plmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts to promote hands-on use of antitick plants at community level have clearly increased as signaled by a worldwide documentation of the plants (Tables 2 and 3) and many more studies being conducted on field surveys and trials [58, 109, 122, 129, 149] and laboratory tests [73, 96, 215220]. The ongoing workshops, community-based training seminars, and novel projects on antitick plants at the Intermediate Technology Development Group-Eastern Africa (ITDG-EA), an international nongovernmental organization [129], are other promising proliferation signals in this area.…”
Section: Potential and Future Prospects For The Use Of Antitick Plmentioning
confidence: 99%
“…Some of these plants were among the 43 plant species evaluated in Jamaica, whose crude ethanol extracts of the leaves for pesticidal effects on the engorged cattle tick, Boophilus microplus , were determined [57, 58]. Their acaricidal indices (AI) for the crude plant extracts ranged from 50 to 100.…”
Section: Figurementioning
confidence: 99%
“…Kumwarubaine ( (1988), Cabral et al (1996), Mansingh and Williams (1998), Borges et al (2003) P Stoll (1988, Neupane (1992), Berger (1994), Kroschel (1996), Batcher (2000) Af Chen et al (1996), Nardo et al (1997, Vellaikumar (1997) B Andrei et al (1990, Zakir et al (1991), Villamil et al (1995), HerbWeb (2000) I Al-Sharook et al (1991), Arias et al (1992), Isman et al (1996), Cabral et al (1996), Nardo et al (1997, Valladares et al (1997), Adoyo et al (1997), Schmidt et al (1998) Grieve (1931), Watt and Breyer-Brandwijk (1962), Duke and Wain (1981), Morton (1981), Perry (1980), Duke (1983c) B, F Killip and Smith (1935), Fanshawe (1948Fanshawe ( , 1953, Watt and Breyer-Brandwijk (1962), Abourashad et al (1999), van Andel (2000), Onge Cremlyn (1978), Stoll (1988), Matzigkeit (1990), Juliette de Ba Levy (1991), …”
Section: Appendix 1 An Enumeration Of the Documented Plants And Planmentioning
confidence: 99%
“…I ITDG and IIRR (1996), ICIPE Annual Report (1998/99), Mansingh and Williams (1998), Mulla and Su (1999), Ndumu et al (1999) Williams (1993), ITDG and IIRR (1996), ICIPE Annual Report (1998/99), Ndumu et al (1999), Wilson and Mansingh (2002), Blair and Mansingh (2002), Abdel-Shafy and Zayed (2002), Mansingh and Williams (2002) …”
mentioning
confidence: 99%
“…Matsmura (1985) reported that among six roteniods which occur naturally from T. vogelii, rotenone was found to be the most insecticidal which can act as either a contact or stomach poison, while Dibenzyltrisulfide, an insecticidal compound isolated from P. alliacea, acts as repellant (Mansingh and Williams 1998). This was probably why pods and grains from the unsprayed plants were severely damaged compared to the plant extracts treated plants.…”
Section: Discussionmentioning
confidence: 99%